Analisis Keterkaitan Nilai – Nilai Spiritual Kristiani para Pedagang Tradisional terhadap Penentuan Harga Jual : (Studi pada Pasar Rakyat Waiwerang Kecamatan Adonara Timur Kabupaten Flores Timur) (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This study aims to analyze the relationship between Christian spiritual values and the practice of setting selling prices by traditional traders in Waiwerang People's Market, East Adonara Sub-District, East Flores Regency. Spiritual values such as brotherhood, honesty and gratitude are the main focus in understanding how the traders set prices and carry out their economic activities. This research used a qualitative approach with data collection methods through in-depth interviews with a number of traders and buyers. The results show that traders in Waiwerang Market apply two pricing techniques, namely cost-based pricing and based on their Christian spiritual values. The cost-based technique is carried out by calculating the initial capital, transportation costs, and reasonable profit, while still considering the buyer's condition. Meanwhile, value-based techniques reflect the influence of Christian values in buying and selling practices, such as giving discounts to repeat buyers, adding goods to buyers in need, or being honest in conveying product quality. Economic activities in this market not only reflect commercial transactions, but also contain a deep spiritual dimension, where faith in God and love for others become the main basis for economic decision-making.